2021
DOI: 10.1109/taffc.2019.2902091
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Induced Emotions of Movie Audiences from Multimodal Information

Abstract: Recognizing emotional reactions of movie audiences to affective movie content is a challenging task in affective computing. Previous research on induced emotion recognition has mainly focused on using audiovisual movie content. Nevertheless, the relationship between the perceptions of the affective movie content (perceived emotions) and the emotions evoked in the audiences (induced emotions) is unexplored. In this work, we studied the relationship between perceived and induced emotions of movie audiences. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…A high CCC value indicates high agreement between the values of the predicted scores and ground truth. This means that prediction and ground truth values are similar to each other, and general trend changes for both signals are the same [40]. We compared the predictions of pairs of regression models by means of two-sided Wilcoxon signed rank tests at a 0.05 significance level [51].…”
Section: Experiments 61 Experimental Methodologymentioning
confidence: 97%
“…A high CCC value indicates high agreement between the values of the predicted scores and ground truth. This means that prediction and ground truth values are similar to each other, and general trend changes for both signals are the same [40]. We compared the predictions of pairs of regression models by means of two-sided Wilcoxon signed rank tests at a 0.05 significance level [51].…”
Section: Experiments 61 Experimental Methodologymentioning
confidence: 97%
“…The analyzed color images were then transformed into color measurement values and visualized as a graph. Emotion words were matched according to the highest corresponding measurement values [ 36 , 37 ].…”
Section: Configuration and Designmentioning
confidence: 99%
“…Annotating interfaces such as PAGAN (Melhart et al, 2019 ) or CARMA (Girard, 2014 ) (see section 3.3.2.2 for more details on annotation tools) have been developed to collect affect ratings by participants experiencing medias. However, researcher must be careful when using the movie or audio extracts as an emotion induction method, as it was found that perceived emotions by the observer (i.e., interpretation of the movie content, e.g., emotions of a movie character perceived by the observer) do not always agree with induced emotions (i.e., emotions felt by the observer)—both when using video (Muszynski et al, 2019 ) and audio (Kallinen and Ravaja, 2006 ).…”
Section: Common Emotion Elicitation Techniques Used For Data Collementioning
confidence: 99%